Evolution of spatiotemporal patterns in vegetation net primary productivity and the driving forces on the Loess Plateau - Mao, Shenglin; Shangguan, Zhouping (Frontiers in Environmental Science, 2023)
To address global warming, the carbon sequestration capacity by net primary productivity (NPP) in vegetation on the Loess Plateau (LP) is particularly important as it allows us to adjust the vegetation restoration strategies in response to global changes. However, the spatial correlation of NPP and its impact on vegetation restoration remains unclear. MOD17A3 remote sensing products analyzed the temporal and spatial changes in NPP on the LP over the last two decades (2000–2020). The resulting spatial autocorrelation indices identified cold and hot spots in the spatial clustering patterns. Finally, the effects of climate change and human activities on the anomalous clustering of NPP were assessed using Person correlation analysis and multi-temporal land use land cover (LULC) data. The results indicate (ⅰ) From 2000 to 2020, the NPP of the LP increased significantly by 6.88 gCm^(-2) 〖yr〗^(-1), and the proportion of revegetated land area > 400 gCm^(-2) 〖yr〗^(-1)increased from 4 % (2000) to 37 % (2020). The spatial distribution pattern of NPP had an increasing trend from northwest to southeast; (ⅱ) The vegetation NPP on the LP had a strong positive global spatial autocorrelation (p < 0.01). The hot and cold regions had obvious polarization, in which the cold spots were clustered in the northwest, and the hot spots were distributed in the south and east. The spatial clustering patterns were dominated by high-high (HH) and low-low (LL) clusters. Abnormal patterns mainly existed in the transition areas between HH and LL clusters and insignificant regions, which were jointly affected by human activities and climate change. (ⅲ) Precipitation was the dominant climatic factor (86.31 %) affecting the variation of NPP on the LP, with the annual minimum precipitation showing a synergistic relationship with the interannual variability in NPP and the maximum precipitations greatly influenced the variation in local spatial anomaly patterns. Therefore, climatic extremes affect vegetation. Our research improves our understanding of the driving mechanisms involved in the regional carbon cycle and provides a reference for green ecological management and high-quality development in the LP.